Gliosarcoma with neuroaxis metastases. (30th November 2015) - Ramos, Rui; Morais, Nuno; Silva, Ana Isabel; Almeida, Rui
Abstract : Gliosarcomas are rare tumours of the central nervous system, with a well-known capacity for metastasis. When they metastasise, the dissemination occurs more frequently via the haematogenous route to extraneural sites. Metastasis-spread through the cerebrospinal fluid is extremely rare. We present the case of a 58-year-old man who underwent a gross total resection of a lesion in the left temporal lobe. The histological findings revealed a gliosarcoma and the patient received radiotherapy followed by chemotherapy. Seven months after surgery, while the patient remained neurologically intact, brain and spinal cord MRI revealed tumour recurrence and neuroaxis metastases through the traffic routes of the cerebrospinal fluid. The patient died 8 months after the diagnosis. A PubMed search regarding metastatic gliosarcoma up to June 2015 was also carried out. To the best of our knowledge, this is the first case report of gliosarcoma metastases to the brain and spinal cord leptomeninges.